Updated catalog and generic keys of the Leiodidae (Insecta: Coleoptera) of the Neotropical region (“Latin America”: Mexico, the West Indies, and Central and South America) - Peck, Stewart B.; Gnaspini, Pedro; Newton, Alfred F. (Zootaxa, 2020)
This paper presents an updated catalog of all taxa of Leiodidae (s.lat.) reported from the Neotropical Region. Keys are presented for the identification of all subfamilies, tribes, and 62 described genera. Three undescribed genera are included in the keys. A total of 600 valid named species are listed, with type localities, type depositories, synonyms, distributions, and biologies where known, and some unnamed species as recorded in the literature. Many species remain to be described. In this work we formally establish no new synonyms and no new combinations although we may indicate the existence of these; but we add new records for described species, and we make spelling corrections of scientific names, when appropriate. A brief review of distribution patterns is given. The fauna has been derived partly from some Nearctic elements that have penetrated as far south as Bolivia. A few genera in the Neotropical element have penetrated the Nearctic Region as far north as the northern U.S.A. or southeastern Canada. Most of the Neotropical genera are autochthonous. In southern South America there is a diverse Neo-Austral fauna with clear “Transantarctic” relationships to Australia and New Zealand and weakly to southern Africa. Some genera variously occur on other continents.